Dynamic risk prediction of BK polyomavirus reactivation after renal transplantation - Fang, Yiling; Zhang, Chengfeng; Wang, Yuchen; Yu, Zhiyin; Wu, Zhouting; Zhou, Yi; Yan, Ziyan; Luo, Jia; Xia, Renfei; Zeng, Wenli; Deng, Wenfeng; Xu, Jian; et al. (Frontiers in Immunology, 2022)
Purpose: To construct a dynamic prediction model for BK polyomavirus (BKV) reactivation during the early period after renal transplantation and to provide a statistical basis for the identification of and intervention for high-risk populations. Methods: A retrospective study of 312 first renal allograft recipients was conducted between January 2015 and March 2022. The covariates were screened using univariable time-dependent Cox regression, and those with P<0.1 were included in the dynamic and static analyses. We constructed a prediction model for BKV reactivation from 2.5 to 8.5 months after renal transplantation using dynamic Cox regression based on the landmarking method and evaluated its performance using the area under the curve (AUC) value and Brier score. Monte-Carlo cross-validation was done to avoid overfitting. The above evaluation and validation process were repeated in the static model (Cox regression model) to compare the performance. Two patients were presented to illustrate the application of the dynamic model. Results: We constructed a dynamic prediction model with 18 covariates that could predict the probability of BKV reactivation from 2.5 to 8.5 months after renal transplantation. Older age, basiliximab combined with cyclophosphamide for immune induction, acute graft rejection, higher body mass index, estimated glomerular filtration rate, urinary protein level, urinary leukocyte level, and blood neutrophil count were positively correlated with BKV reactivation, whereas male sex, higher serum albumin level, and platelet count served as protective factors. The AUC value and Brier score of the static model were 0.64 and 0.14, respectively, whereas those of the dynamic model were 0.79±0.05 and 0.08±0.01, respectively. In the cross-validation, the AUC values of the static and dynamic models decreased to 0.63 and 0.70±0.03, respectively, whereas the Brier score changed to 0.11 and 0.09±0.01, respectively. Conclusion: Dynamic Cox regression based on the landmarking method is effective in the assessment of the risk of BKV reactivation in the early period after renal transplantation and serves as a guide for clinical intervention.